2023
DOI: 10.1088/1674-1137/ace67f
|View full text |Cite
|
Sign up to set email alerts
|

On the microscopic shell-model version of the Bohr-Mottelson collective model

Abstract: Recently proposed microscopic shell-model version of the
Bohr-Mottelson (BM) collective model is considered in more detail in
coordinate representation. The latter possesses a clear and
transparent physical meaning, which allows to reveal some features
of the new version of the collective model missed in the previous
formulation. The relationships to the original BM model are
considered, as well as between the different limiting submodels of
the microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Recently, a microscopic shell-model version of the BM model was formulated [40,41] within the framework of the microscopic proton-neutron symplectic model (PNSM) of nuclear collective motion with dynamical algebra. This version provides an interesting and relevant shell-model symplectic-based framework to explore the nature of the observed nuclear collective dynamics.…”
Section: S P(12 R)mentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, a microscopic shell-model version of the BM model was formulated [40,41] within the framework of the microscopic proton-neutron symplectic model (PNSM) of nuclear collective motion with dynamical algebra. This version provides an interesting and relevant shell-model symplectic-based framework to explore the nature of the observed nuclear collective dynamics.…”
Section: S P(12 R)mentioning
confidence: 99%
“…The many-particle states in the microscopic shellmodel version of the BM model are classified by the following dynamical symmetry chain [40,41]: 1) 6) SO (2) where below the different subgroups are given the quantum numbers that characterize their irreducible representations. The quantum numbers and p define the oscillator shell structure.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the BM model was embedded [16,17] into the two-component shell-model theory within the framework of the PNSM. It was demonstrated that a microscopic shellmodel version of the BM model is defined by one of dynamical symmetry chains of the PNSM.…”
Section: Introductionmentioning
confidence: 99%